2011
DOI: 10.1245/s10434-011-1818-9
|View full text |Cite
|
Sign up to set email alerts
|

Features Associated with Successful Recruitment of Diverse Patients onto Cancer Clinical Trials: Report from the American College of Surgeons Oncology Group

Abstract: Background The clinical trials mechanism of standardized treatment and follow-up for cancer patients with similar stages and patterns of disease is the most powerful approach available for evaluating the efficacy of novel therapies, and clinical trial participation should protect against delivery of care variations associated with racial/ethnic identity and/or socioeconomic status. Unfortunately, disparities in clinical trial accrual persist, with African Americans (AA) and Hispanic/Latino Americans (HA) under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Many of these barriers have a disproportionate effect on minority enrollment because members of minority populations are more likely to receive care at under-resourced hospital systems where few clinical trials are available, to be underinsured, and to present with comorbidities that make them ineligible for trials that may be available. 2830 …”
Section: System-level Barriersmentioning
confidence: 99%
“…Many of these barriers have a disproportionate effect on minority enrollment because members of minority populations are more likely to receive care at under-resourced hospital systems where few clinical trials are available, to be underinsured, and to present with comorbidities that make them ineligible for trials that may be available. 2830 …”
Section: System-level Barriersmentioning
confidence: 99%
“…Considered as the gold standard, 5 clinical trials offer scientifically rigorous approaches to develop and evaluate better and/or safer anti-neoplastic interventions, with the ultimate goal of establishing new practice standards. 6 As a result, the major advances in cancer treatment have emerged from clinical trials. 7 Participating in most clinical trials offers benefits to patients such as the provision of the state-of-the-art care compared to a potentially more effective intervention and improved survival.…”
mentioning
confidence: 99%
“…Combined with strategies to overcome social, economic, and communication barriers to trial recruitment will improve our ability to realize the potential of novel drugs in development. 14,15 …”
Section: Discussionmentioning
confidence: 99%
“…14, 15 The importance of a trial infrastructure and active trial portfolio management has been strikingly demonstrated in the United Kingdom, through the establishment of the NCRN in 2001. 9 This has led to a 3-fold increase in trial recruitment from less than 3.5% to the current 12% of incident cases, and an increase from 39% to 74% in the number of trials that have met their recruitment targets on schedule.…”
mentioning
confidence: 99%